2012
DOI: 10.1021/ed200185e
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry Outreach Project to High Schools Using a Mobile Chemistry Laboratory, ChemKits, and Teacher Workshops

Abstract: The Chemistry Outreach Program (ChOP) of Virginia Tech was a university-based outreach program that addressed the needs of high school chemistry classes in underfunded rural and inner-city school districts. The primary features of ChOP were a mobile chemistry laboratory (MCL), a shipping-based outreach program (ChemKits), and teacher workshops. ChOP targeted schools that lacked basic chemistry equipment and resources, as well as schools where science teachers had limited training in chemistry. The MCL, a fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Therefore, when MCPL is used instead of simulation used by [32], this results in increased conceptual understanding. This is also similar to a study by [4] which showed that student learning using experiments was better than field trips such as a visit to a museum and other informal science experiences. Therefore, low achievement in the topic of Forces and Motion can be increased by using MCPL.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Therefore, when MCPL is used instead of simulation used by [32], this results in increased conceptual understanding. This is also similar to a study by [4] which showed that student learning using experiments was better than field trips such as a visit to a museum and other informal science experiences. Therefore, low achievement in the topic of Forces and Motion can be increased by using MCPL.…”
Section: Discussionsupporting
confidence: 88%
“…Teachers gain more benefits in terms of improve skills in conducting experiments, along with lessons or teaching and learning sessions. This is aligned with [4] who showed that student engagement towards science learning and teacher ratings were better through mobile labs than field trips and other informal science experiences. The ChemKits program [3] also provided computers and probes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Environmental coursework can easily be adapted to existing curricula ( Wenzel and Austin, 2001 ) and teachers can set the level of complexity based on the students' background (e.g., freshmen vs. senior students) as well as on the available budget. Among the different environmental topics, water quality has been implemented in a few service-learning activities included in analytical and/or environmental chemistry courses during the last decade ( Dameris et al, 2019 ; Jung et al, 2017 ; Schwarz et al, 2016 ; Tomasik et al, 2014 ; Donaghy and Saxton, 2012 ; Long et al, 2012 ; Kammler et al, 2012 ). Most of these activities include the collection and analysis of different water samples.…”
Section: Introductionmentioning
confidence: 99%